2012
DOI: 10.1186/1471-2334-12-281
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged outbreak of Serratia marcescens in Tartu University Hospital: a case–control study

Abstract: BackgroundThe aim of our study was to investigate and control an outbreak and identify risk factors for colonization and infection with Serratia marcescens in two departments in Tartu University Hospital.MethodsThe retrospective case–control study was conducted from July 2005 to December 2006. Molecular typing by pulsed field gel electrophoresis was used to confirm the relatedness of Serratia marcescens strains. Samples from the environment and from the hands of personnel were cultured.ResultsThe outbreak invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
2
12
1
Order By: Relevance
“…(151,152). We did not see any significant differences between non-Serratia LOS and LOS with S. marcescens.…”
Section: Discussioncontrasting
confidence: 53%
“…(151,152). We did not see any significant differences between non-Serratia LOS and LOS with S. marcescens.…”
Section: Discussioncontrasting
confidence: 53%
“…was also found to be present in higher abundance in CD. The phylogenetic microarray targets mainly S. marcescens , which is considered as an opportunistic pathogen able to cause invasive infections (sepsis, meningitis, pneumonitis) in neonates [45,46]. These bacteria may impair the intestinal integrity, but their possible role in CD remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, the organism is capable of causing nosocomial infections in other body systems, most notably respiratory and urinary tract infection, meningitis, bacteremia and different types of wound infection. [5][6][7] Serratia species cause outbreaks in neonatal intensive care units, 8,9 including necrotizing enterocolitis, and have been associated with significant morbidity and mortality in children. 10 However, recent studies showed that 65% of all Serratia infections were community-based, with S. marcescens being the most commonly isolated species, accounting for 92% of all isolated Serratia.…”
Section: Introductionmentioning
confidence: 99%